My side of the story (a journal for teens) - Jara, Lito S. (New Day Publishers, 2013)
"My side of the story is the fourth book written by the author for New Day Publishers. It was originally intended to be used along with the guidance resource book for counselors. temporary Mess (Making a difference for teens). But now it can be used as a separate guidance journal. the book is intended for preteens and teenagers, ages 12-to 16-years old. It is useful tool to help them understand themselves better by allowing them to share their thoughts, feelings, opinions and ideas about their experiences as teenagers in this present generation. It will also help adults to take closer look at our young people today and understand where they are coming from and "listen" to their stories, experiences, inner thoughts and feelings as reflected in this journal, My Side of the Story. This book is available in both printed and eBook format." -- Cover.